Serratia marcescens, Uncommon Pathogen, Causing Orbital Cellulitis in Uncontrolled Diabetes Melitus - Stevie Kresentia; Amir Surya (Vision Science and Eye Health Journal, 2022)
Introduction: Orbital cellulitis is a rare ophthalmic infection. Special attention should be given because it can be fatal, either to vision or life. Case presentation: A 49-year- old man complained of swelling and pain in his left eye for two weeks, along with lethargy and fever. One month previously, the patient was admitted to the hospital with a diagnosis of sinusitis and was planned for surgery, but he refused. He also had a history of uncontrolled diabetes. The examination showed proptosis and adhesions of the upper and lower eyelids covered with crusts. After debridement, his visual acuity was no light perception. There was a lot of necrotic tissue and pus covering the sclera and conjunctiva. Intraocular pressure was soft by palpation. He was planned for hospitalization. The results of the pus culture showed the growth of Serratia marcescens, and the antibiotics usage was following the bacterial culture. Unfortunately, after 72 hours of intravenous antibiotics, there was no clinical improvement. We decided to do evisceration to reduce local infection and prevent the infection spreading systemically. The patient’s condition was gradually improve after surgery. Conclusions: Orbital cellulitis is an infection that can be harmful unless the treatment starts immediately and effectively. Redness and swollen eyelid accompanied by proptosis and painful ocular movement can be critical signs of the disease. Intravenous antibiotics have always been the first choice of treatment. Therefore, culture and antibiotic sensitivity test play an important role in successful treatment. Surgical should be considered if it becomes a life-threatening condition.